PENERAPAN TAX REVIEW ATAS PAJAK PENGHASILAN BADAN DAN WITHHOLDING TAX PADA PT. ABC TAHUN PAJAK 2013 - Ayuningsih, Siti Ro'fah; Setiawan, Putu Ery (E-Jurnal Akuntansi, 2016)
The purpose of this study was to determine the effect of applying a tax review of corporate income tax and withholding tax Income Tax Article 21, 22, 23, 24, 25, 26 and 4 (2) , The method used in this research is descriptive method that compared the results of comparative tax reporting according to the company with the calculation of Income Tax and the Agency for withholding tax in accordance with applicable tax in Indonesia. Results of this study indicate that a review of the corporate income tax in 2013, taxpayers have a deposit and reporting obligations in accordance with the applicable rules and regulations. However, in the calculation and preparation of tax reconciliation report contained several errors in the cost of consumption and telephone. PT. ABC also has obligations cutting, deposit and reporting of Income Tax 21 and 25 in accordance with the provisions of taxation. Based on data from the company for fiscal year 2013, there is no potential for Income Tax Article 22, 23, 24, 26 and 4 (2) outstanding. Normal 0 false false false EN-GB X-NONE X-NONE /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: Tax Review, Corporate Tax and Withholding Tax